A novel treatment for keratitis sicca (Dry eye): Anatomical feasibility study. Issue 6 (6th July 2017) - Iwanaga, Joe; Watanabe, Koichi; Kusukawa, Jingo; Fisahn, Christian; Alonso, Fernando; Oskouian, Rod J.; Tubbs, R. Shane
Abstract : Chronic dry eye (keratitis sicca) is a significant problem that in certain populations can result in corneal desiccation and the potential for blindness. Therefore, novel treatments for such disorders might decrease patient morbidity. The present study aimed to investigate a potential treatment for chronic dry eye via a cadaveric feasibility study. On 10 cadaveric sides, the parotid gland branch of the auriculotemporal nerve (ATN) was identified and anastomosed to an anterior superficial temporal branch (STb) of this same nerve. The STb was then transposed anteriorly and sutured to the lacrimal gland. The parotid branch of the ATN was easily identified on all sides. The STb of the ATN was easily identified and mobilized on all sides. This latter nerve had adequate length to be moved to the ipsilateral lacrimal gland on all sides. Rerouting parotid gland secretomotor fibers to the superficial branch of the ATN and then moving this branch to the lacrimal gland is a feasible surgical maneuver based on our cadaveric study. Clinical studies are now necessary to show utility of this procedure in patients with chronic dry eye. Clin. Anat. 30:839–843, 2017. © 2017Wiley Periodicals, Inc.